Effect of Accelerated Aging on the Mechanical Properties of FFF-Manufactured Polymers - Kohutiar, Marcel; Bednařík, Martin; Labaj, Ivan; Janík, Róbert; Hanzlík, Jan; Krbata, Michal; Zatloukal, Jakub (Manufacturing Technology Journal, 2026)
This study examines the effect of accelerated weathering on the mechanical and viscoelastic properties of thermoplastics produced by fused filament fabrication (FFF). Three polymers, acrylonitrile styrene acrylate (ASA), polyethylene terephthalate glycol (PETG), and polylactic acid (PLA), were subjected to alternating UV radiation and condensation cycles in a QUV chamber simulating environmental exposure. Tensile testing and dynamic mechanical analysis (DMA) were used to evaluate the changes in strength, stiffness, and glass-transition behavior. The results revealed distinct responses depending on the polymer structure. ASA maintained its ductility and even showed improved strength, confirming high UV resistance. PETG exhibited a moderate decrease in strength with negligible change in elongation, indicating partial photo-oxidation but stable viscoelastic behavior. PLA demonstrated the most significant stiffening and a noticeable upward shift of the glass-transition temperature due to crystallization and physical aging. Overall, short-term QUV exposure acted as a conditioning process, enhancing the thermal and structural stability of the tested FFF-printed polymers.
Keywords: Fused filament fabrication; Accelerated weathering; Dynamic mechanical analysis; Tensile strength; Thermoplastics